2006
DOI: 10.1074/jbc.m605876200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Network and Chromosomal Clustering of Genes Involved in Synaptic Plasticity in the Hippocampus

Abstract: Gene transcription is required for establishing and maintaining the enduring form of long term potentiation (LTP). However, the transcriptome and its associated molecular programs that support LTP are not well understood. The purpose of this study was to identify activity-regulated genes (ARGs) and their molecular pathways that are modulated by LTP induction and to investigate the genomic mechanism for coordinating the transcription of ARGs. We performed time course DNA microarray analyses on the mouse dentate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 80 publications
5
63
1
1
Order By: Relevance
“…1). This finding is consistent with several studies of memoryassociated gene expression, which indicate that many long-term memory associated genes are unregulated ∼1 h after behavioral treatments or LTP induction (Levenson et al 2004a;von Hertzen and Giese 2005;Park et al 2006). Furthermore, our earlier bioinformatics and expression array analysis showed that most memory-associated genes regulated at 1 h after behavioral training contain putative c-Rel elements in their DNA upstream regions, within 1 kb of their initiation start site.…”
Section: Discussionsupporting
confidence: 78%
“…1). This finding is consistent with several studies of memoryassociated gene expression, which indicate that many long-term memory associated genes are unregulated ∼1 h after behavioral treatments or LTP induction (Levenson et al 2004a;von Hertzen and Giese 2005;Park et al 2006). Furthermore, our earlier bioinformatics and expression array analysis showed that most memory-associated genes regulated at 1 h after behavioral training contain putative c-Rel elements in their DNA upstream regions, within 1 kb of their initiation start site.…”
Section: Discussionsupporting
confidence: 78%
“…However, because of technical limitations, a genome-wide analysis of activity-dependent gene expression has only recently become possible. High-density oligonucleotide microarrays and differential analysis of library expression (DAzLE) have been used to identify genes in cortical and hippocampal neurons whose expression is acutely altered in response to membrane depolarization, NMDA application, LTP induction, and seizure induction (Altar et al 2004, Hong et al 2004, Park et al 2006. These experiments confirm the presence of several hundred neuronal activity-regulated genes in these cells.…”
Section: The Activity-regulated Gene Expression Program In Neurons: Gmentioning
confidence: 50%
“…However, we found that after novel song exposure, declining RNAs (noveldown) actually outnumbered the increasing ones, and by a large margin (463 vs. 153). Comparatively little attention has been given to understanding the mechanism and function of experiencedependent gene suppression in the brain, despite prior evidence for it in the literature (24)(25)(26)(35)(36)(37). Here we detected enrichment for ion channel protein genes in the novel-down set, including channels for calcium, potassium, and sodium and the AMPA glutamate receptor.…”
Section: Auditory Lobulementioning
confidence: 68%
“…We confirmed the acute activation of familiar ''immediate early genes'' by novel birdsong (Table 2), but found that 20% of detectable transcripts (4,341 of 18,246 different probes) ultimately changed their expression in the 24 h following song exposure (considering both the novel and habituated treatment groups). This is an enormous increase over the number of gene products previously identified as ''activity regulated'' in the songbird brain, although it is not entirely unexpected on the basis of recent studies in rodents (24)(25)(26)(27). In the zebra finch, using a smaller microarray and extensive in situ hybridization analyses, Wada et al described 33 genes that are ''singing regulated'' in other parts of the brain responsible for song production (15).…”
Section: Discussionmentioning
confidence: 99%